Social inequality in the Russian Federation: Regional convergence vs. urban divergence in levels of living - Anna Bufetova (European Regional Science Association (ERSA), 2013)
Social disparities in regions of Russia were increasing since transition started in the 1990s. Policy of budgetary alignment and state social policy carried out in the first 10 years of 2000-th at the expense of redistribution of a resource rent reduced in some degree social inequalities among regions. But social disparities between settlements of different size and status within regions are still even more considerable. This empirical paper attempts to add evidence on the issue of disparities and convergence in levels of living within regions and cities of the Russian Federation (the RF) in the period 2000-2010. Combination of regional and center-periphery aspects allows making more adequate assessment and examination of levels of living inequalities. The study covers 79 regions and 193 cities of the RF with population over 100,000. The paper considers various components of level of living: income, poverty rate, employment, quality and affordability of housing, health care and education and analyzes their differences between regions and between cities and their evolution in time. Further quantitative assessment of level of living in regions and cities is made on the base of synthetic indicator of level of living. Introduced indicator comprises information of different indicators and allows classification of RF regions and cities and evaluation of disparities and convergence of levels of living. The process of convergence of levels of living in regions and in cities and within their groups is studied by use of the traditional measures of convergence. The analysis of dynamics of indicator and convergence equations provides evidence for regional convergence of levels of living. At the same time it discovers divergence and polarization of levels of living in cities of the RF. There are detected two divergent groups of cities with growing homogeneity of levels of living within them and increasing gap between them. The paper investigates determinants of degree and evolution of inequalities in levels of living in cities of the RF. The obtained results allow to conclude that administrative status of city is a crucial determinant of degree, rate of growth and sustainability of level of living. And existing centralization of financial resources on the federal level of budget system facilitates the importance of administrative status for city development and thus reinforces spatial inequality in levels of living. In the last part of the paper I discuss measures of social and institutional policy that can alleviate observed tendency.
Keywords: 330; regional disparities; levels of living; inequality; cities; regional capitals; divergence; Russian Federation